A bi-level programming approach for improving relief logistics operations: A real case in Kermanshah earthquake. (July 2020) - Haeri, Abdorrrahman; Hosseini-Motlagh, Seyyed-Mahdi; Samani, Mohammad Reza Ghatreh; Rezaei, Marziehsadat
Highlights: A bi-level optimization model for designing a disaster relief network. Considering both disaster phases of preparedness and response. An augmented DEA model to determine the best places for positioning relief centers. An extended fuzzy goal programming algorithm to solve the bi-level model. A developed fuzzy approach to cope with the epistemic uncertainty. Abstract: Due to its location on the world dry belt, Iran is known as a disaster-prone country. Regarding such a problem, planning for relief operations in disaster situations seems significant and undeniable. The literature on disaster management has mostly defined their problems in a single-level framework, ignoring the bi-level aspect of such problems in both preparedness and response phases. However, in the context of disaster in the real world, there is normally more than one decision-maker that each of them may have their own objective. In this study, a bi-level multi-objective programming approach is extended to design a pre-positioning and distribution network under disastrous conditions considering both preparedness and response phases. The extended framework takes into account simultaneous planning for the distribution of drug, blood and relief items among disaster victims, and transferring the injured to hospital in order to diminish the adverse effects of potential disasters in the response phase. Additionally, to determine suitable candidate places for locating relief centers in the preparedness phase, a modified version of data envelopment analysis model is utilized, something that is not frequently done for facility location planning in the disaster management field. On the other hand, to solve the bi-level multi-objective programming problem with decision-makers at the upper level (the affected country) and the lower level (the international organization), a fuzzy goal programming algorithm is proposed. Furthermore, a consolidated method with respect to a novel fuzzy measure is developed to keep the considered network safe against the inherent uncertainty. Finally, the extended framework is utilized to solve a case study in Kermanshah, the province of Iran.